Partial thrombosis of the corpus cavernosum: should we dig deeper into coagulopathy disorders?. (6th April 2016) - Gomez Gomez, E.; Campos Hernandez, J. P.; Cazalilla, M.; Triviño, F.; Barbudo, J.; Prieto, R.; Requena Tapia, M. J.
Summary: Partial thrombosis of the corpus cavernosum, also known as partial priapism is a rare condition. The condition is known to be unilateral, and its aetiology is not well known. Usually, symptoms are pain and perineal mass and Magnetic Resonance is needed to confirm the diagnosis. In most cases the treatment is conservative with anticoagulation therapy. We present a case of partial thrombosis of the corpus cavernosum with a Factor V Leyden mutation.